Evaluation of the oil-bearing drilling cuttings processing technology in petrochemical industry under cleaner production: A case study in China. (15th November 2022) - Luo, Zhenhua; Yuan, Guangyao; Cen, Kang; Li, Wei
Abstract: The oil-bearing drilling cuttings (OBDC) produced in the petrochemical industry contain a large number of hydrocarbons, and their direct discharge will not only fail to recover the organic matter, but will also seriously harm the environment. In the process of treating OBDC, the consumption of resources and energy and pollution problems may arise, and the current clean production focusing on reduction, non-hazardous and resourcefulness has become the focus of achieving sustainable development. However, there is a lack of studies that consider treatment technology, resource consumption and utilization, and environmental impact under the perspective of cleaner production. In this paper, by studying the indicators related to cleaner production and the Driving Force-Pressure-State-Impact-Response (DPSIR) model, an evaluation index system for OBDC processing technology in the petrochemical industry under cleaner production is constructed. The evaluation results can provide reference for the selection of OBDC treatment process, and provide direction for the development and promotion of the treatment process. In the evaluation system, the DPSIR model can evaluate and manage the OBDC process from different levels and perspectives. The combination of the G1 method and the C-OWA operator method was used to calculate and analyze the index weights, and the improved matter-element analysis method was used to comprehensively evaluate the treatment of OBDC to determine the treatment of technical methods. The evaluation system is applied to actual cases in China. The results show that the low-temperature extraction technique was the best and the chemical washing method was the lowest compared with the three treatment techniques. The oil removal rate of OBDC, recovery of organic matter, secondary waste gas pollution and other indicators have a great impact on the evaluation of the OBDC treatment process under clean production. In order to contribute to the optimal recovery and utilization of resources, it is recommended to develop improvements to the treatment pair technology treatment process based on the results of the evaluation. Highlights: Analysis of oil-bearing drilling cuttings hazardous waste from the perspective of clean production. Established the evaluation index system of oily drill cuttings treatment process under cleaner production. A new set of oil-bearing drilling cuttings evaluation model under cleaner production was constructed. Apply the improved matter-element analysis method to evaluate and analyze indicators at different levels. Analyze and evaluate actual cases and propose areas for improvement.